2023
DOI: 10.3389/fimmu.2023.1218661
|View full text |Cite
|
Sign up to set email alerts
|

Identification of molecular subtypes based on PANoptosis-related genes and construction of a signature for predicting the prognosis and response to immunotherapy response in hepatocellular carcinoma

Jinfeng Zhu,
Qian Huang,
Xingyu Peng
et al.

Abstract: BackgroundPrevious studies have demonstrated that PANoptosis is strongly correlated with cancer immunity and progression. This study aimed to develop a PANoptosis-related signature (PANRS) to explore its potential value in predicting the prognosis and immunotherapy response of hepatocellular carcinoma (HCC).MethodsBased on the expression of PANoptosis-related genes, three molecular subtypes were identified. To construct a signature, the differentially expressed genes between different molecular subtypes were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…The data of gene counts was used to perform differential expression analysis by a "limma" R package, the standardized TPM matrix was utilized for correlation, survival, mutation, immune, gene set enrichment analysis (GSEA) and drug sensitivity analysis. We extracted 85 PANoptosis-related genes included necroptosis, apoptosis and pyroptosis genes according to previous literatures 13,14,21 , and conducted correlation analysis by "limma" package to identify PANoptosis-related lncRNAs, the ltering criteria was cor 0.3 and pvalue 0.001. Finally, we compared the expression of PANoptosis-related lncRNAs by Wilcoxon test to identify differentially expressed and PANoptosis-related lncRNAs (DPRLs) between normal and tumour tissue.…”
Section: Identi Cation Of Differentially Expressed and Panoptosisrela...mentioning
confidence: 99%
See 1 more Smart Citation
“…The data of gene counts was used to perform differential expression analysis by a "limma" R package, the standardized TPM matrix was utilized for correlation, survival, mutation, immune, gene set enrichment analysis (GSEA) and drug sensitivity analysis. We extracted 85 PANoptosis-related genes included necroptosis, apoptosis and pyroptosis genes according to previous literatures 13,14,21 , and conducted correlation analysis by "limma" package to identify PANoptosis-related lncRNAs, the ltering criteria was cor 0.3 and pvalue 0.001. Finally, we compared the expression of PANoptosis-related lncRNAs by Wilcoxon test to identify differentially expressed and PANoptosis-related lncRNAs (DPRLs) between normal and tumour tissue.…”
Section: Identi Cation Of Differentially Expressed and Panoptosisrela...mentioning
confidence: 99%
“…Recently, it has been reported that PANoptosis against viral infection through innate immune pathway 10 , the tumor necrosis factor-α (TNF-α) and interferon-γ (IFN-γ) induced PANoptosis were found to inhibit tumor growth 11 , and suppression of PANoptosis was proved to promote tumorigenesis 12 . In HCC, some studies have shown that PANoptosis-related genes can predict the prognosis and immunotherapy response [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%